KESIAPAN MENGHADAPI PERUBAHAN PADA GURU SEKOLAH DASAR TERHADAP JENIS BUDAYA DAN DUKUNGAN ORGANISASI - Harahap, Sahala; Wahdi, Hilmy; Wulandini, Wulandini (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
The study investigates the relation of the readiness for change of an elementary school teacher in Jakarta and its vicinity with the kind of organization culture and organizational support he/she experiences from the school. The background is the context of many changes faced by teachers, as a result from changes of government policies related to education, as well as changes affected by the Covid-19 pandemic. The study is quantitative in nature, through questionnaire and statistical analysis, using readiness for change, competing values framework, and perceived organizational support as constructs. Results suggest that in order to have teachers that are ready to change, the school culture should encourage teachers to innovate and adapt, nurturing a healthy relationship and good team building, appreciating teachers’ effort, and providing a clear target and direction.